The Role of Situational Leadership in Manufacturing Industry Decision Making Automation - Desintawati, Alivia Dwi Vivi; Diana, Fita; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2024)
This article examines the role of situational leadership in improving decision-making effectiveness in the manufacturing sector, particularly in relation to automation. The research reveals that a strong understanding of team dynamics and the leader's ability to adjust leadership styles according to employee readiness levels can enhance productivity and motivation. Amid technological and organizational changes, leaders who can adapt quickly will be more effective in managing transitions, especially in automating production processes. This article also offers practical recommendations for leaders to address challenges arising from the implementation of new technologies and to create a more collaborative and innovative work culture. By encouraging employee involvement in decision-making, leaders can foster innovation and improve operational efficiency, which in turn supports the company's success in facing evolving industry challenges.